Fishermen of south Thailand. The malay villagers / Thomas M. Fraser, JR - Fraser, JR. Thomas M. (United Stated of America: Holt, Rinehart and Winston, INC.)
The village and its context, making a livin, the yearly cycle of fishing and rice cultivation, plantations in a cash economy, economic specialists and the market town, the web of life, the family and housebold, the kaampong, neigbbors and kinsmen, the region, kin and ceremonial networks; maintaining control, the good man and his influence, the tambon and the village headman, district, changwat, and nations, dealing with the supernatural, spirits, Illness, and the bomo, fasts, feasts, ad the imam, religion and the crises of life, learning to live in Resembilan, basic values and early training, education, informal, formal, and national, adult status, a resolution of contradictions; the changins scene, technological change and community integration, economic change, from sea to jungle, the Government and plannet change, monority groups and national security
Table of contents, maps, glossary, references cited and recommended reading
Col. Soc
Keywords: 1. CULTURE 2. SOCIAL ANTHROPOLOGY 3. SOCIOLOGY